UPAYA PENINGKATAN KINERJA PEGAWAI NEGERI SIPIL PADA DINAS PERHUBUNGAN KABUPATEN PACITAN - Trisnamurti , Tutik Ani; Wikaningtyas, Suci Utami (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The performance of employees of the Pacitan Regency Transportation Agency needs to be improved, this can be seen from the activities of employees who are still lacking discipline in coming to work. This research method uses qualitative research methods, where data that cannot be calculated or data in the form of information, obtained from interviews with leaders and other employees, so the research method is descriptive in nature supported by data obtained by observation, interviews and involvement with the object of research. The result is that the performance of the Pacitan Regency Transportation Office is still not optimal, due to the low professionalism and specialization of tasks, the lack of time discipline, and the slow process of adoption and adaptation of advanced technology. Meanwhile, the obstacles faced in improving the performance of employees of the Pacitan Regency Transportation Office are the lack of employee motivation and infrastructure, especially computer technology. Efforts to improve the performance of employees of the Pacitan Regency Transportation Agency in this study are viewed from performance which is a multi-dimensional concept covering 3 aspects, namely attitude, ability and achievement. As well as increasing cooperation with the regional government in organizing good training which will later be held by internal and external from the regional government in an effort to improve employee performance at the Pacitan Regency Transportation Office.Kinerja pegawai Dinas Perhubungan Kabupaten Pacitan perlu ditingkatkan lagi, hal ini dapat dilihat dari kegiatan pegawai yang masih kurang disiplin masuk kerja. Metode penelitian ini menggunakan metode penelitian kualitatif, dimana data yang tidak dapat dihitung atau data yang berbentuk informasi, yang diperoleh dari hasil wawancara dengan pimpinan dan pegawai lain, jadi dalam metode penelitiannya bersifat deskriptif yang didukung dengan data yang diperoleh dengan cara observasi, wawancara dan keterlibatan dengan obyek penelitian. Hasilnya kinerja Dinas Perhubungan Kabupaten Pacitan masih belum optimal, karena masih rendahnya profesionalisme dan spesialisasi tugas, masih kurangnya disiplin waktu, dan lambanya proses adopsi dan adaptasi teknologi maju. Sedangkan kendala yang dihadapi dalam peningkatan kinerja pegawai Dinas Perhubungan Kabupaten Pacitan adalah kurangnya motivasi kerja pegawai dan sarana prasarana terutama teknologi computer masih kurang. Upaya peningkatan kinerja pegawai Dinas Perhubungan Kabupaten Pacitan dalam penelitian ini di tinjau dari kinerja yang merupakan suatu konsep yang multi dimensional mencakup 3 aspek yaitu sikap (attitude), kemampuan (ability) dan prestasi (accompllishment). Serta meningkatkan kerja sama dengan pemda dalam penyelenggaraan diklat baik yang nantinya akan diselenggarakan oleh intern dan ekstern dari pemda dalam upaya peningkatan kinerja pegawai di Dinas Perhubungan Kabupaten Pacitan.